Magnetic and processability studies of nitrile rubber vulcanisates containing barium ferrite and carbon black - Soloman, M. A.; Kurian, P.; Anantharaman, Maliemadom R.; Joy, Pattayil Alias (Indian Journal of Chemical Technology, 2005)
Fine particles of barium ferrite (BaFe12O19) belonging to the M-type hexagonal ferrites were prepared by the conventional ceramic techniques. They were incorporated into a nitrile rubber matrix according to a specific recipe for various loadings to produce rubber ferrite composites (RFC)The percolation threshold is not reached for a maximum loading of 130 phr (parts per hundred rubber). Here in this paper, the magnetic properties and processability of the nitrile rubber based RFCs containing barium ferrite (BaF) and HAF carbon black is reported. The magnetic properties of the ceramic ferrite and these rubber ferrite composites were evaluated and it was found that the coercivity values of RFCs were less than that of the ceramic BaF, but remained constant with the loading of both the ferrite filler and carbon black. However, other properties like saturation magnetization and magnetic remanence increased with the loading of ferrite filler.
Keywords: barium ferrite; carbon black; Magnetic materials; nitrile rubber; rubber ferrite composites

Multiferroic behavior of gd based manganite - Sagar, S.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Ferroelectrics, 2009)
Here we report the multiferroic nature of charge ordered manganite Gd0.5Sr0.5MnO3 for the first time. The temperature variation of dielectric constant shows broad relaxor type ferroelectric transition at around 210K and magnetization measurements shows weak ferromagnetism at 50K. The dielectric peak is very close to charge ordering temperature which is an evidence of the link between electronic state and increase of dielectric response. Butterfly variation of capacitance with voltage confirms ferroelectric nature of the sample at room temperature.
Keywords: dielectric constant; manganite; Multiferroic

On the magnetic and dielectric properties of nickel-neoprene nanoconaposites - Jamal, E. Muhammad Abdul; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Materials Chemistry and Physics, 2010)
Nickel nanocomposites were prepared by incorporating nickel nanoparticles in a neoprene matrix according to a specific recipe for various loadings of nickel particles. The dielectric properties of these composites were evaluated for different frequencies ranging from 100 kHz to 8 MHz at different temperatures from 30 degrees C to 120 degrees C. The dielectric permittivity increases with increase of nickel concentration. Increase in temperature enhances the permittivity initially, till 40 degrees C and thereafter the permittivity decreases. The dielectric loss exhibits relaxation peaks and the peaks shift to lower frequencies with increase in volume fraction of the nickel nanoparticles in the matrix. The evaluation of magnetic and dielectric properties of these composites suggests that the dielectric permittivity can be tailored by an appropriate loading of the filler using semi-empirical equations and the magnetic properties vary according to simple mixture equations. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Composite materials; dielectric properties; Elastomers; magnetic properties

On the magnetic, mechanical and rheological properties of rubber-nickel nanocomposites - Jamal, E. Muhammad Abdul; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Polymer Bulletin, 2010)
Rubber-nickel nanocomposites were synthesized by incorporating freshly prepared nanometric nickel particles in two different matrices namely natural rubber and neoprene rubber according to specific recipes for various loadings of nano nickel and the cure characteristics of these composites were evaluated. The maximum torque values register an increase with the increase in loading of nickel in both composites and this is attributed to the non-interacting nature of nickel nanoparticles with rubber matrices. The cure time of natural rubber composites decreases with increase in the content of nickel, and in neoprene rubber cure, time increases with increase in filler content. In natural rubber, the curing reaction seems to be activated by the presence of nickel particles. The magnetization studies of the composites reveal that the magnetic properties of nickel are retained in the composite samples. The elastic modulus of natural rubber and neoprene rubber are largely improved by the incorporation of nickel particles.
Keywords: Cure characteristics; Elastic modulus; magnetic properties; Nanocomposites